أثر المناخ على إنتاج المحاصيل الزراعية في إقليم الساحل والجبال الساحليّة السوريّة - حليمة عبد الكريم; امعلا علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تمّت هذه الدراسة عام 2011م لمعرفة تأثير المناخ على إنتاج المحاصيل الزراعيّة في إقليم الساحل والجبال الساحليّة السوريّة، وكذلك إيجاد العلاقة بين العناصر المناخيّة وإنتاج المحاصيل، ومن ثم إظهار أهميّة المناخ في هذا الإقليم بوصفه إقليماً متميّزاً في سماته وخصائصه عن باقي الأقاليم السوريّة. وتبيّن من خلال دراسة تطور الحيازات الزراعيّة أن المساحة المخصّصة للزراعة لم تزداد لا بل تراجعت، وقد استخدمنا في دراستنا معامل ارتباط بيرسون لدراسة تأثير كل عنصر مناخيّ على حده وأثره على الإنتاج ، وقد تبيّن لنا أنّهُ يجب دراسة العناصر المناخيّة الفاعلة والمنفعلة فيما بينها من خلال دراسة الارتباط المتعدد لهذه العناصر وأثره على الإنتاج لكي تكون الدراسة الكميّة شاملة. تبيّن لنا من خلال تحليل البيانات أن معامل ارتباط كل عنصر مناخيّ وأثره على الإنتاج يفيدنا في فهم قوة هذا العنصر مثال ذلك: تأثير الحرارة، ولكن أثر هذا العنصر يكون ثانوياً عندما تكون العناصر مندمجة فيما بينها كما في الارتباط المتعدد. This study in 2011 was conducted to determine the impact of climate on crop production in the coast and the coastal mountains of Syria, as well as find the relationship between the elements of climate and crop production, and then show the importance of climate in this region as being a distinct region in its qualities and characteristics from the rest of Syrian regions. Through the study of the evolution of agricultural holdings, we found that the space allocated to agriculture has not increased but on the contrary it decreased. We have used in our study, Pearson correlation coefficient to study the effect of each climatic element separately and its impact on production. For our quantitative study to be comprehensive, we must study the elements of climate whether active and passive including the multi-link study of these elements and its impact on production. It has been shown to us through the analysis of the data that the correlation coefficient of each element and its impact on the climate output helps us to understand the power of this element as the heat effect, for example. But the impact of this item will be secondary when the elements are integrated with Pena as in the multi-link.